2010
DOI: 10.2478/v10175-010-0032-4
|View full text |Cite
|
Sign up to set email alerts
|

Heart valve bioprothesis; effect of different acellularizations methods on the biomechanical and morphological properties of porcine aortic and pulmonary valve

Abstract: Abstract. Tissue engineering is a promising tool for the creation of a new type of the heart valve bioprothesis. The biological scaffold composed of decellularized tissue has been successfully used for the constructions of the valve prosthesis. An analysis of the efficiency of the valve leaflet acellularization methods and the influence of those methods on the morphology and the biomechanical properties of the ECM (extra cellular matrix) was performed. Fresh porcine hearts obtained from a slaughterhouse were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
5
0
1
Order By: Relevance
“…Not with standing, decellularized pulmonary valves such as the CryoValve SG pulmonary human valve have been previously cleared and are currently being studied prospectively to determine mortality, reoperation, structural deterioration, thromboembolism, conduit failure, calcification among other adverse events [56][57][58]. Replacement TEPVs developed from biodegradable scaffolds seeded with autologous cells have proven successful in large animal and human models [29,31,[59][60][61]. From a fabrication stand point, the scaffold design is critical; the 3D structure guides cellular migration, attachment and growth [62][63][64].…”
Section: In Vitro Modeling and Fabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…Not with standing, decellularized pulmonary valves such as the CryoValve SG pulmonary human valve have been previously cleared and are currently being studied prospectively to determine mortality, reoperation, structural deterioration, thromboembolism, conduit failure, calcification among other adverse events [56][57][58]. Replacement TEPVs developed from biodegradable scaffolds seeded with autologous cells have proven successful in large animal and human models [29,31,[59][60][61]. From a fabrication stand point, the scaffold design is critical; the 3D structure guides cellular migration, attachment and growth [62][63][64].…”
Section: In Vitro Modeling and Fabricationmentioning
confidence: 99%
“…The ideal scaffold should be optimally biodegradable-the timing of absorption into endogenous tissue should match tissue formation. Scaffolds have been developed from polyglycolic acid (PGA), polylactic acid (PLA), combined PGA-PLA and polyhydroxyoctanoate (PHO) [29,[59][60][61][62][63][64][65]. The advantage with these materials is thermoplasticity, biodegradability and biocompatibility [29,[60][61][62][63][64][65].…”
Section: In Vitro Modeling and Fabricationmentioning
confidence: 99%
“…The tissue biomechanics may depend on various factors, such as the age of the donor and tissue source [ 16 , 17 ]. In the case of tissue-engineering techniques, the acellularization method can also affect the biomechanics and morphology of the tissue [ 18 ]. The storage conditions of the scaffolds could also be an important factor that may affect the mechanical stability and morphology of the bioprosthetic heart valves.…”
Section: Introductionmentioning
confidence: 99%
“…In the course of clinical studies many investigators have assumed the PAC technique as a reference Literature studies and the authors' practical experiences have shown that the accuracy of the thermodilution method depends on many factors (e.g. physical parameters of the indicator, haematological parameters of blood, heart rate, valves diseases [20] and on the way of injecting of the indicator [9,10]) Manufacturers of the patient's monitor devices quoted, that the unreliability of CO measurements by means of thermodilution amounts to about 5% [11,12]. However this value contradicts clinical observations.…”
Section: Introductionmentioning
confidence: 99%